146 A cluster randomised feasibility trial (cRCT) to test the routine use of the needs assessment tool: cancer (NAT:C) in primary care to reduce unmet patient and carer needs and determine the feasibility of a definitive trial. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Johnson, Miriam; Amoakwa, Elvis; Allgar, Victoria; Blenkinsopp, John; Currow, David; Farrin, Amanda; Foy, Robbie; MacLeod, Una; Meads, David; Wright-Hughes, Alexandra; Clark, Joseph
Abstract : Background: People with cancer commonly have distressing symptoms and unidentified palliative care needs. The Needs Assessment Tool:Cancer (NAT:-C) is a validated tool to improve needs-based access to palliative care. Aims: To assess the feasibility and acceptability of conducting a definitive cRCT of the NAT:-C in primary care in terms of Recruiting 4 GP practices and 40–60 patients (plus carers), Uptake of NAT:-C, Questionnaire completion rates, Acceptability of study measures. Methods: A non-blinded cluster randomised trial with parallel process evaluation. Patients with active cancer were identified through cancer registries or in clinic and invited to participate and nominate a carer if they wanted to. Participants completed study questionnaires at baseline and 1, 3 and 6 months. Patients sought a 20 min appointment post-baseline. Patients, carers and GP practice staff were invited to participate in interviews/focus groups. Results: Five GP practices were approached and 4 recruited and trained in the use of the NAT:-C. Practices were cluster randomised (1:1). Forty-seven patients and 17 carers were recruited. Early recruitment problems were addressed by including a pre-paid expression of interest form with the study invitation. Recruitment rate was appropriate for a definitive multicentre trial. 44 (94%) of patients received a study appointment, 42 (95%) attended and 32 (76%) received a NAT-guided consultation. Item completion rates of the proposed primary outcome measure the Supportive Care Needs Survey at baseline were 96.4%. 15 patient interviews and 4 focus groups with GP practices were conducted. Participants supported the need for a definitive study and found all measures acceptable. Process evaluation informed effective refinement of study invitations. Conclusion: The feasibility trial indicated that the recruitment rate, intervention uptake and data collection were appropriate, with refinements, for a definitive cRCT is feasible.